Analisis Pengaruh Perceived Usefulness, Perceived Ease of Use, dan Behavioral Intention terhadap Use Behavior pada Aplikasi Pembelajaran Logika dan Desain Pemrograman di Institut Bisnis dan Informatika Stikom Surabaya - Qoumuddin, Agil Rijal; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Based on data obtained from the Development and Application of Information Technology (PPTI) Institute Business and Information of Stikom Surabaya (Stikom Surabaya), 20% -30% of the students S1 Information Systems has a value under B for the course Programming Logic and Design. This proves that is an obstacle course students. Therefore, they invented Learning Application Programming Logic and Design to help the lecture on this subject. However, during implementation of the evaluation has not been done so that the acceptance of this application, developers and teachers do not know the effect of this application on the user's behavior.Measurement of user behavior of applications and Design Learning Logic Programming using 3 TAM (Technology Acceptance Model 3). This method is carried out to determine the factors that influence user behavior.               Based on the distribution of questionnaires to 126 students S1 Information System that follows the lecture Logic and Design Programming, which is then analyzed by SEM showed that the Interests Behavior (behavioral intention) direct and significant impact on User Behavior (use behavior) while the benefits utilities (perceived usefulness) and Ease of Use (perceived ease of use), and significant indirect effect on User Behavior (use behavior).